Effect of the type of forage (pasture vs. hay) and the inclusion of condensed tannins in ewe’s diet on milk quality and suckling lamb’s growth - Lobón S.; Sanz A.; Blanco M.; Joy M. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The aim of this study was to assess the effects of the type of forage and the inclusion of condensed tannins (CT) on productive parameters of lactating ewes and the lamb’s growth. Thirty-nine Churra Tensina ewe-lamb pairs were used in a 2 x 2 experimental design, with two types of forages: Pasture vs. Hay; and two concentrates: a concentrate with 10% of Quebracho (SYLVAFEED ByPro Q, Spain) extract with 75% of CT (CT) and a control concentrate without CT (Control). At parturition, ewes were randomly distributed according to their body-weight (average 46.6 kg), body condition score (average 2.43) and lambing date (4-Apr.). Ewes were daily fed 300 g of concentrate plus ad libitum forage. The experimental period lasted 35 days. Pasture ewes had greater daily milk production and protein content than hay-fed ones (1.31 vs. 1.00 l/d and 5.1 vs. 4.6%, for milk production and protein content, respectively) but had similar fat content (average 6.4%, P>0.05). The inclusion of CT in the concentrate did not affect milk production (P>0.05) or fat content (P>0.05), but influenced the protein content of milk (4.8 vs. 5.0%, for CT and Control, respectively; P<0.05). Lamb growth during lactation was greater in Pasture than in Hay lots (280 vs. 220 g/d, respectively; P<0.001), regardless of the inclusion of CT. In conclusion, pasture forage improved milk production and composition and lamb growth, whereas the addition of condensed tannins in the ewe diet only had effect on the protein content of milk, decreasing its content.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)